The BASICS Lean Implementation Model : Lean Tools to Drive Daily Innovation and Increased Profitability - Protzman III, Charles W.; Protzman, Daniel; Keen, William; Taylor and Francis (Boca Raton, FL : Productivity Press, 2018)
In 2004 Charlie Protzman created The BASICS Lean Implementation Model, which covers the full spectrum of what is needed to be effective and successful at implementing a Lean System. The reader is taken through a step by step approach developed over the last 15 years, in the use and understanding of Lean tools, principles, and processes. The authors break down Lean concepts to their simplest terms to make everything as clear as possible for Lean practitioners. You will learn an integrated, structured, problem-solving approach identified by the acronym BASICS (Baseline, Analyze, Suggest Solutions, Implement, Check and Sustain) This methodology is combined with a proven business strategy to help ensure a successful and sustainable transformation of any organization. The BASICS approach produces "real" bottom line savings with 20% to 50% or more increases in productivity when compared to pure batching environments. As those who have read the book will tell you, this is not a theory book$1! = (Bbut rather a book you can return to over and over again for reference, throughout your Lean journey.s
1. The BASICS Model Overview -- 2. The BASICS Model: Baseline (B) -- 3. BASICS Model: Assess/Analyze (A) -- 4. BASICS Model: Suggest Solutions (S) -- 5. BASICS Model: Implementation (I) -- 6. BASICS Model: Check (C) -- 7. BASICS Model: Sustain (S)
Includes bibliographical references and index.
Also available in print format.
Keywords: BUSINESS & ECONOMICS / Quality Control; BUSINESS & ECONOMICS / Production & Operations Management; Lean manufacturing; Electronic books